TWO CRITERIA FOR GOOD MEASUREMENTS IN RESEARCH: VALIDITY AND RELIABILITY - Mohajan, Haradhan Kumar (Annals of Spiru Haret University. Economic Series, 2017)
Reliability and validity are two most important and fundamental features in the evaluation of any measurement instrument or toll for a good research. The purpose of this research is to discuss the validity and reliability of measurement instruments that are used in research. Validity concerns what an instrument measures, and how well it does so. Reliability concerns the faith that one can have in the data obtained from use of an instrument, that is, the degree to which any measuring tool controls for random error. An attempt has been taken here to review the reliability and validity, and threat to them in some details.